The Influence of Work Family Conflict, Work Environment and Job Stress on the Performance of Regional General Hospital Employees - Viola Fransiska; Nasution Nasution (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to examine the impact of Work Family Conflict, Work Environment, and Job Stress on employee performance at RSUD Bengkulu Tengah. The research focuses on testing the extent to which work-family conflict affects performance, understanding the influence of the work environment, and analyzing the impact of job stress. The research employs a quantitative design with primary data collection through questionnaires. Random sampling from various divisions ensures population representation. Statistical analysis utilizes Structural Equation Modeling (SEM) with SmartPLS, commonly used in research. The findings indicate that job stress and work-family conflict do not significantly affect performance, while the work environment has a positive and significant impact on RSUD employees' performance. These findings underscore the crucial role of the work environment in enhancing performance and well-being at RSUD Bengkulu Tengah, offering valuable insights for the development of effective policies and management practices.